Optogenetics: Emerging strategies for neuropathic pain treatment - Li, Siyu; Feng, Xiaoli; Bian, Hui (Frontiers in Neurology, 2022)
Neuropathic pain (NP) is a chronic health condition that presents a significant burden on patients, society, and even healthcare systems. However, in recent years, an emerging field in the treatment of neuropathic pain – optogenetic technology has dawned, heralding a new era in the field of medicine, and which has brought with it unlimited possibilities for studying the mechanism of NP and the treatment of research. Optogenetics is a new and growing field that uses the combination of light and molecular genetics for the first time ever. This rare combination is used to control the activity of living cells by expressing photosensitive proteins to visualize signaling events and manipulate cell activity. The treatments for NP are limited and have hardly achieved the desirable efficacy. NP differs from other types of pain, such as nociceptive pain, in that the treatments for NP are far more complex and highly challenging for clinical practice. This review presents the background of optogenetics, current applications in various fields, and the findings of optogenetics in NP. It also elaborates on the basic concepts of neuropathy, therapeutic applications, and the potential of optogenetics from the bench to the bedside in the near future.